BROMINASI ASAM SINAMAT DI BAWAH BEBERAPA KONDISI REAKSI - Simanjuntak, Bonor
In this research, transformation of olefinic double bond of cinnamic acid has been conducted under various reaction condition in order to get 2,3-dibromo-3-fenilpropionic acid as efficient and as effective as possible. Reaction was performed under various solvents, concentrations, atmospheric gas and reaction times. trans-Isomer of cinnamic acid was used as substrate and bromine liquid or gas as brominating agent. Pure product was obtained under the following reaction condition i.e. conser,tration 0,2% cinnamic acid, at room temperature in air. The product was obtained as white crystal. It showed : melting point 200°C, one spot on TLC with Rf (chloroform : aceton = 2:1) = 0,25 ; single peak on VPC, H t= 10.29 min. on OV-17 column. Structure determination by spectroscopic method showed : ultraviolet spectrum (nm) . % = 217,5 (_. _ max 31770) while a band on 270 nm which is specific for vinyl to system does not, appear; infrared spectrum (cm 1 ) °C-Br - 695 (s), while a band at 1620 cm -I which is specific for viaylic system does not appear; II NMR spectrum (ppm) . 5,1-4,33 (2H, d, d, J - 12 Hz; CH -CI) ; 7,5-7,3 (5H, in, ArH) and 9.6 (1HI, b, OH, D 2 0- exch). The ratio of the peak absorbtioa area CH-CH : ArH - 2:5 ;Mass spectrum at m/e= 310 (M + ); base peak 103 and fragment molecular ions at m/e : 227; 183; 147; 103 77; 44, indicate that there are two bromine atoms on the side chain. From the above data it can be concluded that the main product is 2,3-dibromo-3-fenil-propionic acid. Bromination of cinnamic acid in CC1 4 under N 2 seems to follow radical reaction which was initiated by substrat interaction with reagen. The presence of radical inhibitor (0 2 from air) seems to the reaction shift to ionic mechanism Bromination of solid cinnamic acid with bromine gas within 5 and 10 hours gave mix products. The persentage of the main product at 5 hours reaction time is higher than that of 10 hours. The succes of bromination of olefinic double bond of cinnamic acid to produce 2,3-dibromo-3-fenil-propionic acid can be seen from two different points of few : a. If the purity of the dibromide is concerned the reaction should be carried out in CC1 4 , under open air with cinnamic acid consentration of 0,2%, at room temperature. b. If the high persentage of main product is concerned the reaction should be carried out in CC1 4 under N2 with cinnamic acid consentration of 4,4 % at 30°C .